Trends In The Implementation Of Instructional Models In Educational Research: A Systematic Literature Review - Arista Lindi Alvita; Isnandar Slamet; Budi Usodo (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The increasing diversity of instructional models has provided educators with broader alternatives for designing learning experiences that accommodate subject characteristics, learning objectives, and students' needs. At the same time, the growing number of available models has made the selection of an appropriate instructional approach increasingly challenging. This study aims to identify, classify, and analyze the development of instructional models implemented in educational research through a Systematic Literature Review (SLR). The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, including the stages of identification, screening, eligibility assessment, and inclusion of studies retrieved from reputable scientific databases based on predefined selection criteria. The selected articles were analyzed using descriptive and thematic approaches to identify the types of instructional models, research trends, and implementation characteristics across different educational levels. The findings indicate that problem-oriented, collaborative, inquiry-based, and project-based instructional models are the most frequently implemented approaches. Furthermore, the selection of instructional models is influenced by learning objectives, subject characteristics, educational level, and the competencies targeted for development. This review concludes that no single instructional model is universally effective for all learning contexts, highlighting the importance of selecting instructional models that align with specific educational conditions to achieve optimal learning outcomes.